Insidensi streptococcus beta-haemolyt cus pada anak dengan pharyngitis - A. Samik Wahab, A. Samik Wahab (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1977)
Pharynx-swabs using filter paper strip method were done on children with pharyngitis, and 3,8% positive Streptococcus beta-haemolyticus group A and 4,8% positive non-group A werefound.Clinical manifestations were: fever (100%), hyperaemic pharynx with exudate 54%, without exudate 46% and with cough 27%. Blood examinations were done on 40 positive cases of which 60% showed leucocytosis.Months with a high incidence were: January Ã¢â¬â February 27%, May Ã¢â¬â June 36% and September Ã¢â¬â October 27%.